أثر نوع السماد العضوي في نوعية محصول البازلاء - سمرة, بديع; سعيد, هيام (Latakia University Journal -Biological Sciences Series, 2019)
درس تأثير ثلاثة أنواع من الأسمدة العضوية(سماد أغنام, سماد أبقار, زرق دواجن) على نوعية البازلاء الخضراء المنتجة, حيث حسبت النسبة المئوية لكل من المادة الجافة, السكريات الكلية, الأحماض العضوية, فيتامين C , النشاء, البروتين والدهون في البذور المنتجة ,كما حسبت الكمية الكلية لكل من هذه المؤشرات في وحدة المساحة وقورنت مع الشاهد(معاملة دون تسميد) تفوقت معاملة التسميد بزرق الدواجن بتأثيرها في محتوى البذور الخضراء من السكريات الكلية(1.99%) وفيتامين C (39.6مغ/100غ مادة طازجة) على الشاهد(1.8% و34.32 مغ/100غ مادة طازجة), في حين تفرقت معاملة الشاهد على التسميد بزرق الدواجن من حيث نسبة المادة الجافة والنشاء والبروتين في البذور الخضراء . بينت النتائج أن جميع معاملات التسميد العضوي قد تفوقت في كافة المؤشرات المدروسة على الشاهد من حيث الكمية الكلية الناتجة من وحدة المساحة، وحققت معاملة سماد الأغنام أفضل النتائج في محتواها من المادة الجافة الكلية مقدارها 244.4 كغ من الدونم الواحد وكمية من النشاء مقدارها 120.2 كغ/دونم. The effect of three types of organic fertilizers (Sheep manure, Cow dung, Chicken faeces) on the quality of green peas had been studied, where the percentage of dry matter, total sugars, and organic acids, vitamin C, protein and lipids in harvested seeds were calculated, and the total quantity of each in size unit have been calculated and compared to the control (treatment without fertilization). Fertilization with chicken discharge gave the best results for the contents of the green seeds (total sugars 1.99%, vitamin C 39.6 mg/100 g fresh materials) in comparison with the control (1.8%, 34.32mg/100g fresh materials), where the control treatment gave the best results for the percentage of dry matter, starch and protein contents. Results showed that, all organic fertilization treatments were better than the control treatment in the total produced quantity unit, where the sheep discharge fertilization treatments gave the best results (total dry matters 244.4 kg/demon and starch 120.2kg/demon).